Pelatihan dan Pendampingan Teknik Pemasaran yang Efektif pada ISMA'U Nusa Tenggara Barat di Jombang - Sunardi Sunardi; Isah Munfarida; Senang Senang; Moh. Kholik; Ari Kartiko (An Naf'ah: Jurnal Pengabdian Masyarakat, 2025)
The Effective Marketing Techniques training at Pondok Pesantren Al-Urwatul Wutsqo Jombang aimed to enhance the skills of santri in marketing the pesantren to the wider community, especially through digital media. The training utilized methods such as lectures, interactive discussions, demonstrations, and field practice to provide both theoretical understanding and practical skills in marketing. The results of the training showed that participants were able to grasp marketing concepts, utilize social media, and implement persuasive marketing techniques. Despite challenges related to limited time and access to technology, the training successfully equipped santri with the skills needed to market the pesantren effectively. It is expected that this training will contribute positively to enhancing the pesantren’s image and attracting prospective students to join